Disinfection protocols of irreversible hydrocolloid: effect on candida total cell count and dimensional accuracy - Ahmad Zawawi, Nur Dini; Muhammad, Nur Farah Athirah; Nasir, Siti Hajjar; Arzmi, Mohd Hafiz; Ahmad, Norfaezah (2021)
Introduction: Disinfection of impression is compulsory to prevent cross-infection to dental personnel. However, prolonged immersion in disinfectants may affect the dimensional accuracy of irreversible hydrocolloid. Different types of disinfectants are available nowadays, including alcohol-based, glutaraldehyde, and chlorine derivatives. Objectives: To investigate the effect of disinfection protocols on Candida total cell count and dimensional accuracy of irreversible hydrocolloid. Methods: For the antifungal activity part, 60 alginate beads were made and treated with different disinfection protocols (2% Aseptoprint, 1% sodium hypochlorite or 3% MD 520 for two minutes, one hour, six hours or 24 hours) except for control group. The beads were inoculated with Candida albicans (ATCC MYA 4901). Colony-forming units (CFUs) were counted using a haemocytometer and analysed using paired t-test. For dimensional accuracy assessment, alginate impressions were taken from a master cast and treated with the same disinfection protocols. Three linear measurements of the casts from impressions immersed in different disinfection protocols were compared to the master cast. Statistical analysis was determined using Friedman Test. Results: Significant reduction of Candida CFUs were observed after disinfection with 3% MD 520 and 2% Aseptoprint compared to the control (P<0.05). The dimensional changes of alginates treated for six and 24 hours were also found to be statistically significant (P<0.05). Discussion: 3% MD 520 and 2% Aseptoprint had effective antifungal activity on irreversible hydrocolloids impression. Dimensional changes of alginate were due to imbibition and syneresis, affecting the casts constructed. Longer immersion time yielded less fungal count but resulted in increased dimensional changes. Conclusion: 3% MD 520 and 2% Aseptoprint are recommended for irreversible hydrocolloid disinfection, with immersion time not exceeding one hour.